Long-Term Follow-Up after Intravenous Immunoglobulin Therapy in Patients with Severe Ocular Mucous Membrane Pemphigoid Unresponsive to Conventional Therapy - Stefania Leuci; Massimo Amato; Elena Calabria; Raffaele Piscopo; Fausto Tranfa; Gianrico Spagnuolo; Michele Davide Mignogna (Journal of Ophthalmology)
Mucous membrane pemphigoid (MMP) is a heterogeneous group of rare, systemic, autoimmune subepidermal inflammatory disease that affects mucous membranes and the eye. In its most severe forms, this disease needs systemic therapy, usually based on steroids and immunosuppressant agents. In unresponsive cases or in the presence of contraindications or severe side effects due to conventional systemic corticosteroid and/or immunosuppressant therapy, a therapy shift to high-dose intravenous immunoglobulins (IVIg) has been recommended in other reports. This new therapy has proven to be effective in stopping ocular pemphigoid, but the data regarding the long-term effect on the disease activity or reactivation are extremely scarce, so the novel scientific aim of this study was to evaluate the clinical outcomes after a 9-year follow-up in 12 eyes (6 patients) affected by MMP with ocular involvement, successfully treated with IVIg therapy, as previously described in our report published in 2008. The evaluation of ocular and extraocular disease progression was performed at the end of IVIg therapy and at the end of the follow-up period. After 9 years, all the eyes enrolled showed a long-lasting remission of ocular and oral symptoms with a significant steroid-sparing effect. In conclusion, the IVIg has to be considered as a safe and successful alternative therapy in patients with severe ocular mucous membrane pemphigoid; furthermore, this kind of therapy seems to be effective in maintaining the clinical remission by the time.